2022
DOI: 10.3390/app12073245
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing Applications in Orthopaedic Surgery: Clinical Experience and Opportunities

Abstract: Background: Three-dimensional (3D) printing is a technology capable of creating solid objects based on the reproduction of computerised images. This technology offers revolutionary impacts on surgical practice, especially in prosthetic and traumatological surgery. Methods: 20 patients with proximal humeral fractures were divided into two groups, one of which involved the processing of a 3D model. The model made it possible to plan the positioning and dimensions of the implants. The results were then compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In general, the interpretation of imaging data is now actually a process of integrating 2D and 3D images, but in complex fractures of the proximal humerus, with difficult-to-understand spatial structures, the analysis and complete determination of the fracture pathological anatomy are more difficult [ 8 , 11 , 26 ]. The occurrence of iatrogenic complications is not only associated with surgical skill and mastery of theoretical knowledge, but also related to preoperative diagnosis and surgical planning [ 1 ]. This is especially true for junior surgeons and trainees, where hands-on practical experience goes a long way in successfully performing high-demand surgeries [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, the interpretation of imaging data is now actually a process of integrating 2D and 3D images, but in complex fractures of the proximal humerus, with difficult-to-understand spatial structures, the analysis and complete determination of the fracture pathological anatomy are more difficult [ 8 , 11 , 26 ]. The occurrence of iatrogenic complications is not only associated with surgical skill and mastery of theoretical knowledge, but also related to preoperative diagnosis and surgical planning [ 1 ]. This is especially true for junior surgeons and trainees, where hands-on practical experience goes a long way in successfully performing high-demand surgeries [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing a well-defined methodology to create a 1:1 scale 3D-printed model using polytactic acid (PLA) plastic filament [ 1 ], two full-touch anatomical models were created for each patient in group A: a “fracture model” and a “reduction model.” Our academic institution owns the printer, which is made freely available for research purposes. The “fracture model” served as a static representation of the fracture, in which artificial “3D bridges” were included to stabilize and maintain the precise and current positions of the bone fragments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Technical advances have considerably improved medical treatment practices, and 3D printing (3DP) techniques have been applied to the field of orthopedics [7][8][9][10][11][12]. Recently, several studies have shown that 3DP, the rapid prototyping technology, can be used for efficient preoperative plate contouring as per the exact surface of the individualized 3DP bone model [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%